Surrogate humanity : race, robots, and the politics of technological futures - Atanasoski, Neda author.; Vora, Kalindi, author. (Durham : Duke University Press, 2019)
Technoliberalism and automation : racial imaginaries of a post-labor world -- Sharing, collaboration, and the commons in the fourth industrial revolution : the appropriative techniques of technoliberal capitalism -- Automation and the invisible service function : toward an "artificial artificial intelligence" -- The surrogate human affect : the racial programming of robot emotion -- Machine autonomy and the unmanned spacetime of technoliberal warfare -- Killer robots : feeling human in the field of war -- Epilogue: On technoliberal desire, or why there is no such thing as a feminist AI.